Prevalence and Impact of De Novo Donor‐Specific Antibodies During a Multicenter Immunosuppression Withdrawal Trial in Adult Liver Transplant Recipients. Issue 3 (8th February 2019) - Jucaud, Vadim; Shaked, Abraham; DesMarais, Michele; Sayre, Peter; Feng, Sandy; Levitsky, Josh; Everly, Matthew J.
Abstract : The development of human leukocyte antigen (HLA) donor‐specific antibody/antibodies (DSA) is not well described in liver transplant (LT) patients undergoing immunosuppression (IS) withdrawal protocols despite the allograft risk associated with de novo DSA (dnDSA). We analyzed the development of dnDSA in 69 LT patients who received calcineurin inhibitor monotherapy and were enrolled in the ITN030ST study. Of these 69 patients, 40 stable patients were randomized to IS maintenance (n = 9) or IS minimization (n = 31). Nine of the 31 IS minimization patients achieved complete withdrawal and were free of IS. Among patients who achieved stable IS monotherapy 1 year after transplantation, the prevalence of dnDSA was 18.8%. Acute rejections and the biopsy‐proven findings disqualifying patients from IS withdrawal attempt were factors associated with dnDSA development ( P = 0.011 and P = 0.041, respectively). Among randomized patients, dnDSA prevalence was 51.7% after IS minimization and 66.7% in IS‐free patients. dnDSA prevalence in patients on IS maintenance was 44.4%. dnDSA development during IS minimization was a risk factor for acute rejection ( P = 0.015). The majority of dnDSA were against HLA‐DQ antigens (78.7%). Conclusion. During the first year following transplantation, acute rejections increase the risk of developing dnDSA, so dnDSA positivity should be considered for IS withdrawal eligibility; during IS minimization, dnDSA development was associated with acute rejection, which prevented further IS withdrawal attempts.